Rehabilitation strategies for survivors of gender based violence : a case of Musasa Harare Shelter - Mazendame, Glorious S (Midlands State University, 2020)
The researcher sought to study the rehabilitation strategies used by Musasa to assist survivors of Gender Based Violence. The research was enriched with a couple of theories, relevant literature by other authors and previous studies that supported the research. The survivors were sampled using the random sampling method. The researcher used the method to pick on whoever wanted to be interviewed because the research is sensitive and therefore the researcher had to be considerate .In addition for the key informants the researcher used purposive sampling as it was clear whom to interview. The research instruments used were in-depth interviews which constituted demographic data, cases that are in the shelters as well as the rehabilitation strategies used at the shelters. Data was analyzed manually using Microsoft Word to explain the phenomenon. Major findings were that women are actually in need of safe shelters post violence to heal both physically and emotionally. The study also revealed that the four most common types of violence women are facing which are physical violence, sexual violence, emotional abuse and economic abuse. Apart from that, the study revealed that women and girls face gender based violence nommater the age using more of emotional coping strategies and social support strategies. Recommendations were given to the organization on way to improve rehabilitation strategies for survivors of Gender Based Violence.